Nutrient Utilization, Milk Yield and Economics of Production in Crossbred Cows Fed Berseem Hay Meal Supplemented Diet - das, madan mohan; Sultan Singh; P. Sharma; Khem Chand (Indian Journal of Animal Nutrition, 2023)
The  replacement effect  of mustard cake protein with berseem hay meal protein  in concentrate mixture was studied  for nutrient utilization, milk yield and economics of production in  crossbred cows. In the control group(G1), the animals were fed control concentrate mixture with wheat straw ad libitum whereas in the treated  group (G2), 60% N of mustard cake was replaced with berseem hay meal  in the   concentrate mixtures along with wheat straw ad libitum for a period of  two and half months. Both the groups were provided iso-energetic and iso nitrogeneous diet. The intake of dry matter either as percentage of body weight or per kg metabolic body size was comparable between the groups. Similarly, the digestibility of nutrients viz.DM, OM, NDF and ADF were similar in both the groups. Milk yield (7.02 Vs 7.21 kg/d) and composition of milk of animals fed with or without supplementation of BHM   was also non- significantly different indicating that legumes did not change the composition of milk. Feed conversion efficiency for milk production and N utilization efficiency was also similar between the groups. Average daily feeding cost and cost of milk production(Rs/kg 4%FCM) reduced (P